Find the exact value of the following sum 3 − tan ( 2 0 ∘ ) 1 + 3 + tan ( 4 0 ∘ ) 1 + 3 − tan ( 8 0 ∘ ) 1 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Problem Loading...
Note Loading...
Set Loading...
We prove the following identity: x − tan θ 1 + x − tan ( θ − 3 π ) 1 + x − tan ( θ + 3 π ) 1 = x 3 − 3 x 2 tan 3 θ − 3 x + tan 3 θ 3 x 2 − 6 x tan 3 θ − 3 . By the triple angle tangent formula: tan 3 θ = ( 3 tan θ − tan 3 θ ) / ( 1 − 3 tan 2 θ ) , it follows that x = tan θ is a zero of the polynomial P θ ( x ) = x 3 − 3 x 2 tan 3 θ − 3 x + tan 3 θ . Moreover, since tan 3 ( θ + π / 3 ) = tan 3 ( θ − π / 3 ) = tan 3 θ , it follows that some of the zeros of the polynomial P θ ( x ) include x = tan θ , tan ( θ + π / 3 ) , tan ( θ − π / 3 ) . Since P θ ( x ) is a monic cubic polynomial, we conclude that these must be all the roots and obtain the following factoring identity: P θ ( x ) = ( x − tan θ ) ( x − tan ( θ − 3 π ) ) ( x − tan ( θ + 3 π ) ) . The desired identity is obtained from expressing P θ ′ ( x ) / P θ ( x ) in two different ways: one using the above factoring formula and the other using the unfactored form of P θ ( x ) .
To obtain the value of the expression in question, we substitute x = 3 and θ = π / 9 = 2 0 ∘ into the main identity. This yields 3 − tan ( 2 0 ∘ ) 1 + 3 + tan ( 4 0 ∘ ) 1 + 3 − tan ( 8 0 ∘ ) 1 = 2 3 .